A theoretical NMR study of selected benzazoles Comparison of GIPAW and GIAO-PCM (DMSO) calculations - Marín-Luna, Marta (Magnetic resonance in chemistry : MRC, 2018)
Copyright © 2017 John Wiley & Sons, Ltd.